PENERAPAN PERATURAN DAERAH KOTA TANGERANG NOMOR 7 TAHUN 2004 TENTANG LARANGAN KEGIATAN PERMAINAN LAYANG-LAYANG BAGI KESELAMATAN PENERBANGAN - Rifqy Praharso; H.K. Martono (Jurnal Hukum Adigama, 2021)
The kite game is a game that is prohibited around the Soekarno-Hatta Airport area as regulated in the Tangerang City Regional Regulation Number 7 of 2004 because it can threaten aviation safety. However, the current socialization and sanctions given by local authorities to the community are still far from expectations and have not been able to optimally have a positive impact on society. The author raises this thesis, with the aim of knowing the extent to which the effectiveness of law enforcement of the Tangerang City Regional Regulation Number 7 of 2004 concerning the Prohibition of Flying or Raising Kites and / or Similar Games and Other Activities that Disrupt Aviation Safety at Soekarno-Hatta Airport and its surroundings. also know the obstacles and efforts of the Tangerang City Government and related stakeholders in enforcing this Regional Regulation. To discuss the above problems, in this study the author uses the Normative research method. Based on data through interviews, it is known that there are still people who commit violations. The faculties that become obstacles for stakeholders are related to the enforcement of the Regional Regulation, namely, legal factors, law enforcement factors, facilities or facilities factors and community factors that are obstacles to overcoming kite games in Neglasari, Benda, Batuceper, and Sepatan Districts. These factors influence the implementation of the Tangerang City Regional Regulation Number 7 of 2004 concerning the Prohibition of Flying or Raising Kites and / or Similar Games and Other Activities that Disrupt Aviation Safety.